A Novel Dirofilaria Species Causing Human and Canine Infections in Hong Kong - TO, Kelvin K. W; WONG, Samson S. Y; YUEN, Kwok-Yung; POON, Rosana W. S; TRENDELL-SMITH, Nigel J; NGAN, Antonio H. Y; LAM, Jacky W. K; TANG, Tommy H. C; AHCHONG, Ah-Kian; KAN, Joshua Chi-Hang; CHAN, Kwok-Hung (Journal of Clinical Microbiology, 2012)
Article Usage Stats Services JCM Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue JCM About JCM Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JCM RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0095-1137 Online ISSN: 1098-660X Copyright © 2014 by the American Society for Microbiology. For an alternate route to JCM .asm.org, visit: JCM